2021
DOI: 10.1007/s10433-021-00645-3
|View full text |Cite
|
Sign up to set email alerts
|

Economic vulnerability and unmet healthcare needs among the population aged 50 + years during the COVID-19 pandemic in Europe

Abstract: This study investigated the effect of economic vulnerability on unmet needs during the first wave of the coronavirus disease 2019 (COVID-19) epidemic in Europe among adults aged 50 years and older using data from the regular administration of the Survey of Health, Ageing and Retirement in Europe (SHARE) and the specific telephone survey administered regarding COVID-19 (SHARE Corona Survey). It addressed three main research questions: Did people who were in difficult economic situations before the epidemic face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Inequalities not only ran along the lines of SEP but also at the intersection with age and gender. Contractions in hospital utilisation were larger among the oldest subjects, a result that emerged also from a European multinational study, 14 possibly linked to a greater fear of the infection consequences. We also found that women, especially those more disadvantaged, experienced larger drops in hospital access than men, another finding reported by previous researches.…”
Section: Discussionmentioning
confidence: 81%
“…Inequalities not only ran along the lines of SEP but also at the intersection with age and gender. Contractions in hospital utilisation were larger among the oldest subjects, a result that emerged also from a European multinational study, 14 possibly linked to a greater fear of the infection consequences. We also found that women, especially those more disadvantaged, experienced larger drops in hospital access than men, another finding reported by previous researches.…”
Section: Discussionmentioning
confidence: 81%
“…The SHARE Corona dataset contains data collected via computer-assisted telephone interviews (CATI) in the two rounds of the SHARE Corona Survey (SCS) between June and August 2020 (1st SCS) and one year later between June and August 2021 (2nd SCS) [17]. We included only people aged 50+ years in agreement with other SHARE studies [18,19], since the SHARE study was specifically designed for better understanding of prevention, protection, and treatment information for the population that is aged 50+ years [16].…”
Section: Sample and Datamentioning
confidence: 99%
“…When it comes to population groups that have felt this pandemic's most harmful health consequences, older people, especially those with chronic illnesses, can be placed at the top of the vulnerability scale. Many studies have confirmed that the elderly have been the most vulnerable group during the pandemic [see, e.g., (58) or (59)]. Barriers to accessing adequate healthcare triggered many negative consequences for the current health status of older adults.…”
Section: Discussionmentioning
confidence: 99%